Fatal Poisoning Cases in a Teaching Hospital of West Bengal: a Descriptive Cross-Sectional Clinico-epidemiological Study - Ankur Bhattacharjee; Saptarshi Chatterjee; Partha Sarathi Hembram; Sobhan Kumar Das (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Poisoning is a global health issue and one of the leading causes of morbidity and mortality inIndia. Pattern of poisoning depends on factors, such as availability of poisons, socioeconomic status of thepopulation, religious and cultural influences, thus creating varied epidemiological trends across time andregions. The present study is planned to address the epidemiological profiles of fatal poisoning cases, withreference to the gastric findings during autopsy.Methods: This is a descriptive, observational, cross-sectional study analysing 184 fatal poisoning cases,who attended to R.G. Kar Medical College Police Mortuary during the period of 2014-2015.Conclusion : People of age group 20-29 years were mostly affected, with a male preponderance and anincidence of 8.03%. People from the rural regions constituted more than 80% of the study sample, withsuicide as the commonest manner of death. Organophosphorus compounds and acids were the mainlydetected, with mucosal congestion and submucosal hemorrhage of stomach as the most reported findings.The authors feel that a prospective study is an option, which could accurately identify the cases and deaths,which could formulate stringent measures so as to decrease the morbidity and mortality due to poisoning.